Tuftelin and HIFs expression in osteogenesis - Bobek, Jan; Oralova, Veronika; Kratochvilova, Adela; Zvackova, Ivana; Lesot, Herve; Matalova, Eva (Histochemistry and cell biology, 2019)
Tuftelin was originally discovered and mostly studied in the tooth, but later found also in other organs. Despite its wide distribution among tissues, tuftelin's function has so far been specified only in the formation of enamel crystals. Nevertheless, in many cases, tuftelin was suggested to be associated with cellular adaptation to hypoxia and recently even with cell differentiation. Therefore, we aimed to investigate tuftelin expression along with hypoxia-inducible factors (HIFs) during the early development of the mandibular/alveolar (m/a) bone, when osteoblasts started to differentiate in vivo and to compare their expression levels in undifferentiated versus differentiated osteoblastic cells in vitro. Immunohistochemistry demonstrated the presence of tuftelin already in osteoblastic precursors which were also HIF1-positive, but HIF2-negative. Nevertheless, HIF2 protein appeared when osteoblasts differentiated, one day later. This is in agreement with observations made with MC3T3-E1 cells, where there was no significant difference in tuftelin and Hif1 expression in undifferentiated vs. differentiated cells, although Hif2 increased upon differentiation induction. In differentiated osteoblasts of the m/a bone, all three proteins accumulated, first, prenatally, in the cytoplasm and later, particularly at postnatal stages, they displayed also peri/nuclear localization. Such a dynamic time-space pattern of tuftelin expression has recently been reported in neurons, which, as the m/a bone, differentiate under less hypoxic conditions as indicated also by a prevalent cytoplasmic expression of HIF1 in osteoblasts. However, unlike what was shown in cultured neurons, tuftelin does not seem to participate in final osteoblastic differentiation and its functions, thus, appears to be tissue specific.
Keywords: Dental Enamel Proteins; Hypoxia-Inducible Factor 1; Intramembranous; buňky 3T3; osteogeneze; HIF2; HIF1; imunohistochemie; Ossification; kultivované buňky; Bone; Animals; Transcription Factors; Immunohistochemistry; transkripční faktory; zvířata; myši; faktor 1 indukovatelný hypoxií; Cells, Cultured; proteiny zubní skloviny; Osteogenesis; Mice; Tuftelin; 3T3 Cells